(untitled) (Editora Impacto Científico, 2025)
This study aimed to analyze the relevance of Environmental Sustainability Management in Food and Nutrition Units (FNUs), focusing on the interconnection between Food Waste reduction and the Rationalization of Critical Resources. The methodology was based on a data search conducted in the SciELO database, seeking studies on plate waste, leftovers, and environmental management practices in food services. Results indicate that the high rate of waste in the institutionalized collective is a critical indicator that significantly impacts FNU costs. The adoption of sustainability programs, such as the Green Kitchen certification, demonstrates that food waste reduction, combined with water and solid waste management, transforms the FNU into an active agent of Sustainable Development. It is concluded that the nutritionist must lead the integrated implementation of these practices, utilizing waste control as a diagnostic tool and promoting team awareness for environmental efficiency. DOI: https://doi.org/10.56238/edimpacto2025.090-038